Evaluation of the Epithelial Barrier Function and Ileal Microbiome in an Established Necrotic Enteritis Challenge Model in Broiler Chickens - Latorre, Juan D.; Adhikari, Bishnu; Park, Si H.; Teague, Kyle D.; Graham, Lucas E.; Mahaffey, Brittany D.; Baxter, Mikayla F. A.; Hernandez-Velasco, Xochitl; Kwon, Young M.; Ricke, Steven C.; Bielke, Lisa R.; Hargis, Billy M.; et al. (Frontiers in Veterinary Science, 2018)
Necrotic enteritis (NE) is a recognized multifactorial disease that cost annually to the poultry industry around $2 billion. However, diverse aspects related to its presentation are not completely understood, requiring further studies using known induction experimental models. Therefore, the purpose of this study was to measure the changes occurring in performance, intestinal integrity and ileal microbiome using a previously established NE-challenge model. Chickens were assigned to a negative control group (NC) or a positive control group (PC). In the PC, broilers were orally gavaged with Salmonella Typhimurium (1 x 107 cfu/chick) at day 1, Eimeria maxima (2.5 x 104 oocyst/chick) at day 18 and Clostridium perfringens (1 x 108 cfu/chick/day) at 23-24 days of age. Weekly, body weight (BW), body weight gain (BWG), feed intake (FI) and feed conversion ratio (FCR) were evaluated. Morbidity and mortality were determined throughout the study, and NE lesion scores were recorded at day 25. Additionally, blood and liver samples were collected to measure gut permeability as determined by levels of serum fluorescein isothiocyanate-dextran (FITC-d) and bacterial translocation (BT). Ileal contents were processed for 16S rRNA gene-based microbiome analysis. Performance parameters and intestinal permeability measurements were negatively impacted in the PC resulting in elevated serum FITC-d and BT with a -6.4% difference in BWG. The NE lesion score in PC (1.97 vs 0.00) was significantly higher in comparison to NC, although there was no difference in mortality. The microbiome analysis showed a dramatic shift of ileal microbiomes in PC groups as compared to NC (ANOSIM: R = 0.76, P = 0.001). The shift was characterized by reduced abundance of the phylum Actinobacteria (P < 0.01), and increased abundance of the genera Butyrivibrio, Lactobacillus, Prevotella and Ruminococcus in PC compared to NC (P < 0.05). Expectedly, Clostridium was found higher in PC (2.98 ± 0.71%) as compared to NC (1.84 ± 0.36%), yet the difference was not significant. In conclusion, results of the present study showed the different intestinal epithelial and microbiological alterations occurring in an established NE-challenge model that considers paratyphoid Salmonella infections in young chicks as an important predisposing factor for presentation of NE.